2018
DOI: 10.1002/pmic.201700366
|View full text |Cite
|
Sign up to set email alerts
|

A Multi‐Omics Analysis of Glycine max Leaves Reveals Alteration in Flavonoid and Isoflavonoid Metabolism Upon Ethylene and Abscisic Acid Treatment

Abstract: Phytohormones are central to plant growth and development. Despite the advancement in our knowledge of hormone signaling, downstream targets, and their interactions upon hormones action remain largely fragmented, especially at the protein and metabolite levels. With an aim to get new insight into the effects of two hormones, ethylene (ET) and abscisic acid (ABA), this study utilizes an integrated proteomics and metabolomics approach to investigate their individual and combined (ABA+ET) signaling in soybean lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 60 publications
1
33
0
Order By: Relevance
“…The extent of changes (>10-fold for some flavonoid glycosides) suggests they represent direct effects of the genetic manipulation and thus of the increase in ABA in LCYb-overexpressing fruits, compared to the less pronounced alterations observed in primary metabolites, which are likely to represent secondary effects. This hypothesis finds support in a series of previous studies linking ABA and flavonoid levels in apple (Lu et al, 2017), soybean (Gupta et al, 2018) and tomato (Mou et al, 2015). In agreement with biochemical data, a series of key structural phenylpropanoid genes was up-regulated in LCYb-overexpressing fruits: for instance, PHENYLALANINE AMMONIA-LYASE (PAL) at the MG and B stages, and CHALCONE SYNTHASE (CHS) at the MG and B+10 stages.…”
Section: Metabolic Alterations In Lcyb-overexpressing Fruitssupporting
confidence: 83%
“…The extent of changes (>10-fold for some flavonoid glycosides) suggests they represent direct effects of the genetic manipulation and thus of the increase in ABA in LCYb-overexpressing fruits, compared to the less pronounced alterations observed in primary metabolites, which are likely to represent secondary effects. This hypothesis finds support in a series of previous studies linking ABA and flavonoid levels in apple (Lu et al, 2017), soybean (Gupta et al, 2018) and tomato (Mou et al, 2015). In agreement with biochemical data, a series of key structural phenylpropanoid genes was up-regulated in LCYb-overexpressing fruits: for instance, PHENYLALANINE AMMONIA-LYASE (PAL) at the MG and B stages, and CHALCONE SYNTHASE (CHS) at the MG and B+10 stages.…”
Section: Metabolic Alterations In Lcyb-overexpressing Fruitssupporting
confidence: 83%
“…A recent multi-omics study with soybean leaves has revealed that exogenously applied ABA increases the accumulation of glycerolipids, prenol lipids, and phospholipids while the concentrations of secondary metabolites, such as flavonoids and isoflavonoids, remain unchanged [37]. Drought stress is known to have a distinct effect on the metabolism of lipids that play a role in maintaining membrane integrity and preserving cell compartmentation [38,39].…”
Section: Table 3 Relative Quantification Of Lc-ms/ms-based Metabolitementioning
confidence: 99%
“…In order to examine the reproducibility of the obtained TMT-data among different biological and technical replicates of the same sample, multi-scatter plots were generated using Perseus software. Scatterplots of the same samples showed a typical non-uniform spread, suggesting low accuracy and reproducibility for the peptides which are closer to the background level [12]. Pearson correlation coefficients of different replicates of the same samples were more than 0.980, indicating a high degree of correlation among different replicates of the same samples ( Figure 3A).…”
Section: High-throughput Quantitative Proteome Analysismentioning
confidence: 96%
“…Protein extraction, trypsin digestion and TMT labeling were carried out as described previously [10]. In brief, proteins from the control and TSWV infected leaves of susceptible and resistant cultivars were extracted using Tris-Mg/NP-40 buffer (0.5 M Tris-HCl (pH 8.3), 2% v/v NP-40, 20 mM MgCl 2 ) followed by TCA/Acetone precipitation of the proteins [12]. Trypsin digestion by the FASP method [52], TMT-labeling [9] and MS analysis [53,54] were carried out as described previously.…”
Section: Protein Extraction Tmt Labeling and Q-exactive Ms Analysismentioning
confidence: 99%